Sejarah Hukum Lingkungan di Indonesia - nafi' mubarok (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
This paper aims to obtain a comprehensive understanding of various legal instruments related to the environment through an understanding of environmental law from its historical aspects. The law evolves and progresses throughout the historical development of society and not legislated as a complete system of conduct from the first time it presented. This paper concludes several points; the first point is that the historical regulation of Environmental Law in Indonesia that can be classified into three periods; the Dutch East Indies period, the Japanese period, and the period after independence. The second point is that after Indonesian independence, there are three legal regulations on the environment were regulated, namely: (1) Law No. 4 of 1982 concerning Basic Provisions for Environmental Management (UULH), (2) Law No. 23 of 1997 concerning Environmental Management (UUPLH), and (3) Law No. 32 of 2009 concerning Environmental Protection and Management (UUPPLH). Each of these laws has different features and characteristics but comes intending to perfect the previous law